2011
DOI: 10.1088/0266-5611/27/7/075004
|View full text |Cite
|
Sign up to set email alerts
|

Optimal geometry toward uniform current density electrodes

Abstract: Electrodes are commonly used to inject current into the human body in various biomedical applications such as functional electrical stimulation, defibrillation, electrosurgery, RF ablation, impedance imaging, and so on. When a highly conducting electrode makes direct contact with biological tissues, the induced current density has strong singularity along the periphery of the electrode, which may cause painful sensation or burn. Especially in impedance imaging methods such as the magnetic resonance electrical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…This, however, could mean imposing many more constraints and higher computational burden. A simpler yet more effective solution may be to design electrodes that distribute the current across electrode-scalp interface more uniformly by, for example, varying the sponge depth through the electrode [49]. …”
Section: Discussionmentioning
confidence: 99%
“…This, however, could mean imposing many more constraints and higher computational burden. A simpler yet more effective solution may be to design electrodes that distribute the current across electrode-scalp interface more uniformly by, for example, varying the sponge depth through the electrode [49]. …”
Section: Discussionmentioning
confidence: 99%
“…It can be seen that the highest current density magnitudes seem to be located on the electrode sponge-scalp interface (e.g., Song et al, 2011). Further, the impact of high conducting CSF can be clearly seen with higher current density magnitudes values close to the injecting electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…The current density of 2 A/m 2 adopted in the present study is at the lower end of both safety ranges reported above. It is worth noting that the copper electrode used in this study usually has strong edge singularity (Song et al 2011) as can be seen from figure 2. Carbon-Hydrogel electrodes or optimal geometry recessed electrodes (Song et al 2011) which are supposed to produce more uniform current density distributions should be investigated in future studies.…”
Section: Conclusion and Discussionmentioning
confidence: 97%